Long-term cultivation drives dynamic changes in the rhizosphere microbial community of blueberry - Che, Jilu; Wu, Yaqiong; Yang, Hao; Wang, Shaoyi; Wu, Wenlong; Lyu, Lianfei; Li, Weilin (Frontiers in Plant Science, 2022)
Rhizosphere microbial communities profoundly affect plant health, productivity and responses to environmental stress. Thus, it is of great significance to comprehensively understand the response of root-associated microbes to planting years and the complex interactions between plants and rhizosphere microbes under long-term cultivation. Therefore, four rabbiteye blueberries (Vaccinium ashei Reade) plantations established in 1988, 2004, 2013, and 2017 were selected to obtain the dynamic changes and assembly mechanisms of rhizosphere microbial communities with the increase in planting age. Rhizosphere bacterial and fungal community composition and diversity were determined using a high-throughput sequencing method. The results showed that the diversity and structure of bacterial and fungal communities in the rhizosphere of blueberries differed significantly among planting ages. A total of 926 OTUs in the bacterial community and 219 OTUs in the fungal community were identified as the core rhizosphere microbiome of blueberry. LEfSe analysis revealed 36 and 56 distinct bacterial and fungal biomarkers, respectively. Topological features of co-occurrence network analysis showed greater complexity and more intense interactions in bacterial communities than in fungal communities. Soil pH is the main driver for shaping bacterial community structure, while available potassium is the main driver for shaping fungal community structure. In addition, the VPA results showed that edaphic factors and blueberry planting age contributed more to fungal community variations than bacterial community. Notably, ericoid mycorrhizal fungi were observed in cultivated blueberry varieties, with a marked increase in relative abundance with planting age, which may positively contribute to nutrient uptake and coping with environmental stress. Taken together, our study provides a basis for manipulating rhizosphere microbial communities to improve the sustainability of agricultural production during long-term cultivation.